1988
DOI: 10.1002/oms.1210230107
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of positively charged aliphatic epoxides. II. [C5H10O]+˙ epoxides and α,β unsaturated ethers

Abstract: The unimolecular dissociations of C, epoxides ions monoor disubstituted at C, give exclusive loss of CH, and exclusive formation of methoxyvinyl carbenium ion, both in the source and in the 2nd field-free region. In the case of the 1,2-disubstituted ion in the 2nd field-free region the loss of ethene is the only pathway, while a competition occurs for the trisubstituted ion leading to [C3H60]"' and [C,H,O]+' ions, the structure of which are demonstrated. The first step of the different mechanisms is the cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Typically, the isomerization occurs by bond cleavage of a cyclic molecular ion or by an internal hydrogen abstraction. Thus the distonic ion "CH2-O-CH ~-may be formed by cleavage of the C-C bond in oxirane radical cations [11], and an intermolecular hydrogen abstraction is usually the initial step for the loss of H20 and related elimination processes (see Schemes 2 and 4). Clearly the mechanism of the elimination depends critically on the properties of the initially formed distonic ion as a reactive intermediate.…”
Section: Intermediate Distonic Ionsmentioning
confidence: 99%
“…Typically, the isomerization occurs by bond cleavage of a cyclic molecular ion or by an internal hydrogen abstraction. Thus the distonic ion "CH2-O-CH ~-may be formed by cleavage of the C-C bond in oxirane radical cations [11], and an intermolecular hydrogen abstraction is usually the initial step for the loss of H20 and related elimination processes (see Schemes 2 and 4). Clearly the mechanism of the elimination depends critically on the properties of the initially formed distonic ion as a reactive intermediate.…”
Section: Intermediate Distonic Ionsmentioning
confidence: 99%
“…•+ species may be explained by postulating the intermediacy of INCs. 18,19 In contrast to most categories of C n H 2n O…”
Section: Introductionmentioning
confidence: 97%
“…Various reviews 1-5 summarise the intriguing chemistry that has been reported for a wide range of ionised C n H 2n O species, including aldehydes and ketones, [6][7][8][9][10][11][12] alkenols and cycloalkanols [13][14][15] and cyclic ethers. [16][17][18][19] Many C n H 2n O •+ species undergo hydrogen transfer and even skeletal isomerisation before dissociating. Distonic ions 20,21 and ion-neutral complexes (INCs) [22][23][24][25][26][27][28] frequently are of crucial importance in the rearrangements which precede fragmentation of these ions.…”
Section: Introductionmentioning
confidence: 99%